Mastering SolidWorks : the Design Approach, 3rd Edition - Zeid, Ibrahim; Brown, Nathan (Peachpit Press, 2021)
Thoroughly updated for SolidWorks 2021, Mastering SolidWorks, Third Edition, illuminates solid modeling CAD techniques for developing parts, assemblies, and drawings. Additional specializations, SolidWorks toolboxes, and manufacturing techniques are also included, including such as sheet metal, injection molding, and animation. The goal is to develop CAD skills in students with little or no previous solid modeling expertise, and to hone specialization skills in more advanced students. Students who successfully complete this book should be capable of obtaining SolidWorks Associate and Professional certification. New illustrations reflect SolidWorks 2021 throughout, and this edition fully reflects changes in workflow since the Second Edition (SolidWorks 2014).